2007
DOI: 10.1016/j.plantsci.2006.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis and identification of genes related to potassium transporter families in rice (Oryza sativa L.)

Abstract: Potassium (K +) is an important macronutrient and the most abundant cation in higher plants which plays a key role in various cellular processes. Its accumulation from soil and its distribution throughout diverse plant tissues is mediated by transporter proteins. In plants, different transport systems are known to be involved in the uptake and release of K + from the cells. Though most of the information about the putative K + transporters and their phylogenetic relationships is available in Arabidopsis, it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
69
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 118 publications
0
69
0
1
Order By: Relevance
“…This study showed A. thaliana HKT gene was placed in group IV separated from O. sativa or T. aestivum. Comparative analysis of rice K+ channels also revealed that Arabidopsis is quite distant from rice (Amrutha et al, 2007). There was very high sequence variation among HKT-related genes (overall pairwise mean distance was 1.13).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…This study showed A. thaliana HKT gene was placed in group IV separated from O. sativa or T. aestivum. Comparative analysis of rice K+ channels also revealed that Arabidopsis is quite distant from rice (Amrutha et al, 2007). There was very high sequence variation among HKT-related genes (overall pairwise mean distance was 1.13).…”
Section: Resultsmentioning
confidence: 96%
“…Phylogenetic trees of each family define the evolutionary relationships of the members to each other. In each family, closely related isoforms and separate subfamilies of K + transporters existed, indicating possible redundancies and specialized functions (Amrutha et al, 2007). To meet this challenge of world hunger, it is important to understand the mechanisms of salt tolerance to utilize the unused salt-affected land.…”
Section: Introductionmentioning
confidence: 99%
“…Manual Bock et al, 2006), while transporter genes account for approximately 5% of all rice (Oryza sativa) genes (Amrutha et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorus (P) can affect photosynthesis indirectly through its effects on Calvin cycle enzymes and enzymes related to the synthesis of protein, RNA, and DNA (Walker et al 2014(Walker et al , 1986Warren and Adams 2002). Potassium (K) plays an important role related to stomatal behavior, enzyme activity, photosynthesis, and osmotic adjustment (Amrutha et al 2007;Si et al 2015). Further, foliar element ratios, e.g., C/N (foliar carbon:nitrogen ratio), C/P (foliar carbon:phosphorus ratio), and N/P (foliar nitrogen:phosphorus ratio), are also key traits of ecological relevance and link with d 13 C through their correlation with water use efficiency (WUE).…”
mentioning
confidence: 99%